An Inter-Processor Communication (IPC) Data Sharing Architecture in Heterogeneous MPSoC for OFDMA - Trio Adiono; Rian Ferdian; Febri Dawani; Imran Abdurrahman; Rachmad Vidya Wicaksana Putra; Nur Ahmadi (Journal of ICT Research and Applications, 2018)
Multiprocessor system-on-chip (MPSoC) promises better data management for parallel processing than conventional SoC. This feature is very suitable for wireless communication systems. Better data processing management can reduce resource utilization and can potentially reduce power consumption as well. Hence, this research aimed to minimize the orthogonal frequency-division multiple access (OFDMA) processing hardware by proposing a new data sharing architecture on a heterogeneous MPSoC platform that incorporates inter-processor communication (IPC), multi-processor, multi-bus, multi-frequency and parallel processing design of the medium access controller (MAC) layer. This MPSoC was designed based on a RISC processor with an AMBA multi-bus system. To achieve high throughput, the proposed MPSoC runs at two different frequencies, 40 MHz and 80 MHz. The proposed system was implemented and verified using FPGA. The verification results showed that the proposed system can work in real-time with a maximum throughput of 11 MBps using a 40 MHz system clock. The proposed MPSoC is a promising solution to perform OFDMA processing on 4G and 5G technologies.